Middle-throughput LC-MS-based Platelet Proteomics with Minute Sample Amounts Using Semiautomated Positive Pressure FASP in 384-Well Format - Loroch, Stefan; Panagiotidis, Eleftherios; Klewe, Kristoffer; Swieringa, Frauke; Heemskerk, Johan W.M.; Lerch, Jan-Paul; Greinacher, Andreas; Walter, Ulrich; Jurk, Kerstin; John, Tobias; Barkovits, Katalin; Dandekar, Thomas; Marcus, Katrin; Balkenhol, Johannes (Thrombosis and Haemostasis, 2025)
Comprehensive characterization of platelets requires various functional assays and analytical techniques, including omics disciplines, each demanding a separate aliquot of the given sample. Consequently, sample material for each assay is often highly limited, necessitating the downscaling of methods to work with just a few micrograms of platelet protein.Here, we present a novel sample preparation platform for proteomics analysis using only 3 μg of purified platelet protein, corresponding to 2 × 106 platelets, which can be obtained from approximately 2 to 8 μL of blood from a healthy individual (1.5 × 105–4.5 × 105 platelets/μL) or approximately 100 μL of blood from a patient with severe thrombocytopenia (<2 × 104 platelets/µL).Using this platform, we detected a significant fraction of key players in the platelet activation cascade and, most importantly, identified 36 clinically relevant platelet disease markers even with a non-state-of-the art instrument. This makes LC-MS-based proteomics a highly attractive alternative to conventional assays, which often require milliliters of blood. Our platform transitions from our previously established 96-well proteomics workflow (PF96), which has been successfully employed in numerous platelet proteomics studies, into the 384-well format. This transition is accompanied by (1) a more than two-fold increase in sensitivity, (2) improved reproducibility, (3) a four-fold increase in throughput, allowing 1,536 samples to be processed per lab worker per week, and (4) reduced sample preparation costs.Thus, LC-MS-based platelet proteomics offers a compelling alternative to immunoaffinity assays (which depend on antibody availability and quality), as well as to genomic assays (which can only reveal genotypes). In summary, in conjunction with recent advances in LC-MS instrumentation, our platform represents a highly valuable tool for rapid phenotyping of platelets in research with extraordinary potential for future employment in companion or routine diagnostics.
Keywords: proteomics; platelets; platelet disease markers; platelet signaling; throughput; PF96; PF384; 96-well format; 384-well format